PENGARUH ETIKA PROFESI, INDEPENDENSI, KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL TERHADAP KETEPATAN PEMBERIAN OPINI AUDITOR (Studi empiris pada Kantor Akuntan Publik kota Medan dan Pekanbaru) - Silvia Hellena; Kamaliah -; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of professional ethics, independence, intellectual, emotional intelligence, spiritual intelligence to the accuracy of granting the auditor's opinion. This study conducted on public accounting firm Medan and Pekanbaru, where auditors as samples in this study. Sampling was done by using purposive sampling, with a sample of 104 respondents. the type of data used in this research is primary. method of data collection is done by using a questionnaire. Data analysis techniques using multiple linear regression analysis with SPSS version 20. The results provide evidence that did not affect the independence of the precision of the provision of the auditor's opinion on the level of significance (α) of 5%. While professional ethics, intellectual, emotional intelligence and spiritual intelligence affect the accuracy of granting the auditor's opinion on the level of significance (α) of 5%.Keywords: Ethich profession, Independence, Intellectual, Auditors Opinion.